2018
DOI: 10.1002/aoc.4678
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on catalytic activity of manganese porphyrins with cationic, anionic and uncharged meso substituents: Indirect evidence on the nature of active oxidant species

Abstract: Oxidation of cyclohexene and styrene with sodium periodate and tetra-nbutylammonium periodate (TBAP) catalyzed by MnT(3-MePy)P(OAc), MnT(4-SO 3 )PP(OAc) and MnTPP(OAc) has been studied in water, methanol, acetonitrile and dichloromethane as solvents. The results show significant dependence of the product distribution on the type of solvent and the electronic nature of the aryl substituents introduced at the porphyrin periphery. While the oxidation of cyclohexene and styrene in the presence of MnT(3-MePy)P(OAc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…As we focused mainly on commercially remunerative products, we executed the experiment to analyze the effect of diverse solvents on the epoxidation of styrene which has significant effect on the product distribution. [37] The study of effect of different solvents on the epoxidation of styrene was aimed to reduce the other byproduct formation and to increase the major key yield. A very little conversion was observed with solvents like toluene, DMF and acetonitrile ( Figure 6).…”
Section: F I G U R E 4 Tem Images Of Go Andmentioning
confidence: 99%
“…As we focused mainly on commercially remunerative products, we executed the experiment to analyze the effect of diverse solvents on the epoxidation of styrene which has significant effect on the product distribution. [37] The study of effect of different solvents on the epoxidation of styrene was aimed to reduce the other byproduct formation and to increase the major key yield. A very little conversion was observed with solvents like toluene, DMF and acetonitrile ( Figure 6).…”
Section: F I G U R E 4 Tem Images Of Go Andmentioning
confidence: 99%
“…Also, Mohajer et al found spectroscopic evidence for the formation of high valent oxo manganese porphyrin species in the presence of hydrogen bond donor additives under homogeneous conditions. [ 44 ] Furthermore, the product distribution upon the oxidation of olefins with periodate [ 41 ] and iodosylarenes [ 45 ] was shown to provide evidence on the nature of active oxidant species; the observation of allylic products in the oxidation of olefins such as cyclohexene also the formation of benzaldehyde in the oxidation of styrenes are in accord with the formation of the high valent Mn‐O species as the active oxidant. As was explained above (Section 3.5), no allylic products were observed in the oxidation of cycloocetene and indene.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the formation of allylic products necessitates the presence of high valent oxo manganese(V) porphyrin species. [ 41,42 ] Also, the abstraction of methyl from styrene and formation of benzaldehyde required a similar mechanism. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of organic compounds with periodate on tungsten polyoxometalate (POM) is the first report on the activation of periodate by d 0 transition metals. It is noteworthy that the presence of a cocatalyst (imidazoles or pyridines) was most often necessary to achieve an acceptable conversion value in the oxidation of organic substrates catalyzed by metalloporphyrins and metal Schiff base complexes. Also, in the case of the d n transition-metal complexes, the formation of high-valent metal oxo species with higher oxidizing ability than the corresponding six-coordinate periodato intermediates ,, led to the overoxidation of organic substrates such as sulfides and a decrease in the selectivity of the reaction toward sulfoxides. As shown in various studies, ,,, the formation of high-valent metal oxo species is significantly facilitated in water and organic solvents containing water or hydrogen-bond donors such as alcohols.…”
Section: Introductionmentioning
confidence: 99%